Radiological Dose Assessment due to the Presence of Norms in the Top Soil of the Imo State Polytechnic, Imo State Nigeria - Benedict Chukwudi Eke; Chijioke M Amakom; Udoka Mathias Ukewuihe; Idowu Richard Akomolafe; Benedict Ositadimma Ejelonu; Benjamin Okechukwu Okereke (SAGE Publishing, 2022)
A study on the radiological dose assessment due to the presence of natural radionuclides in the top soil of Imo state Polytechnic was carried out using a gamma spectroscopic method. From the activity concentrations of natural radionuclides in the topsoil, the absorbed dose rate and annual effects of doses were established. The activity concentrations ranged from 59.20 to 203.78 Bqkg −1 , 8.74 to 45.78 Bqkg −1 , and 12.73 to 44.01 Bqkg −1 for the radionuclides 40 K, 226 Ra, and 232 Th respectively. The absorbed dose rates ranged from 16.70 to 52.10 nGyh −1 while the indoor and outdoor annual effective doses ranged from 20.48 to 63.89 µSvy −1 and 81.94 to 255.58 µSvy −1 respectively. From the results, it shows that the radiation from natural radionuclides in the top soil posed no radiological threat to the population of the institution.